Study of feasibility and efficacy of neoadjuvant chemotherapy in cases of locally advanced breast cancer - Arun V Dawle; Satish Girebinwad (MRIMS Journal of Health Sciences, 2015)
Chemotherapy regimens most commonly used are Bonnadonna designed CMF (Cyclophosphamide Methotrexate 5fluorouracil), doxorubicin based CAF (Cyclophosphamide Adriamycin 5fluorouracil) or AC (Adriamycin Cyclophosphamide) regimen along with hormonal therapies which have been shown to significantly control disease progression, relief from symptoms and improve survival. Because of substantial evolution in the management of advanced breast carcinoma neoadjuvant treatment with chemotherapy is being used increasingly with minimal possible side-effects. Hence CAF and CMF have been tried in the present study to observe the feasibility and efficacy of neoadjuvant chemotherapy in cases of locally advanced breast cancer. CMF (Cyclophosphamide Methotrexate 5fluorouracil) was used in 66.67% of cases and, doxorubicin based CAF (Cyclophosphamide Adriamycin 5fluorouracil) was used in 33.33% of cases. All patients on chemotherapy developed the side effects of GIT, Hematological and alopecia. Of all the patients, 25 needed all six cycles of chemotherapy, three were given only one cycle and two patients were given only two cycles of chemotherapy. Radiotherapy was given in 92% of patients. The response of advanced breast cancer to treatment with combination chemotherapy along with hormonal therapy is an index of nature of the carcinoma and this response provide a guide for the selection of further treatment. Therefore, careful serial recording of the objective measurements of any change in lesions is invaluable as an aid in evaluating the nature of the response.